Disturbance of Self in Borderline Personality Disorder: An Integrative Approach - (:unkn) unknown (My University, 2013)
Disturbance of self has long been recognized as an important aspect of Borderline Personality Disorder. While it has received much attention from theorists, relatively little empirical study has examined the issue. One reason is the difficulty in conceptualizing and operationalizing the associated phenomena. This thesis reviews the theoretical and empirical literature on the self and its disturbance in BPD. It takes an integrative approach, drawing from cognitive, behavioral, psychodynamic, and neurobiological viewpoints. Within this context it presents a model of self disturbance in BPD, organizing processes by time scale as well as types of phenomenological self.
Keywords: Borderline Personality Disorder; Default Mode Network; Identity; Self